Novel endogenous N-acyl amides activate TRPV1-4 receptors, BV-2 microglia, and are regulated in brain in an acute model of inflammation - Raboune, Siham; Stuart, Jordyn M.; Leishman, Emma; Takacs, Sara M.; Rhodes, Brandon; Basnet, Arjun; Jameyfield, Evan; McHugh, Douglas; Widlanski, Theodore; Bradshaw, Heather B. (Frontiers in Cellular Neuroscience, 2014)
A family of endogenous lipids, structurally analogous to the endogenous cannabinoid, N-arachidonoyl ethanolamine (Anandamide), and called N-acyl amides have emerged as a family of biologically active compounds at TRP receptors. N-acyl amides are constructed from an acyl group and an amine via an amide bond. This same structure can be modified by changing either the fatty acid or the amide to form potentially hundreds of lipids. More than 70 N-acyl amides have been identified in nature. We have ongoing studies aimed at isolating and characterizing additional members of the family of N-acyl amides in both central and peripheral tissues in mammalian systems. Here, using a unique in-house library of over 70 N-acyl amides we tested the following three hypotheses: 1) Additional N-acyl amides will have activity at TRPV1-4, 2) Acute peripheral injury will drive changes in CNS levels of N-acyl amides, and 3) N-acyl amides will regulate calcium in CNS-derived microglia. Through these studies, we have identified 20 novel N-acyl amides that collectively activate (stimulating or inhibiting) TRPV1-4. Using lipid extraction and HPLC coupled to tandem mass spectrometry we showed that levels of at least 10 of these N-acyl amides that activate TRPVs are regulated in brain after intraplantar carrageenan injection. We then screened the BV2 microglial cell line for activity with this N-acyl amide library and found overlap with TRPV receptor activity as well as additional activators of calcium mobilization from these lipids. Together these data provide new insight into the family of N-acyl amides and their roles as signaling molecules at ion channels, in microglia, and in the brain in the context of inflammation.